Wild Musa Species Collection of Purwodadi Botanic Garden: Inventory and Its Morpho-taxonomic Review - Hapsari, Lia (Journal of Tropical Life Science, 2014)
Indonesia, being part of the center of origin of bananas (Musaceae), has a large number diversity of bananas both wild seeded species and edible seedless cultivated varieties. Inventory of wild Musa species in Purwodadi Botanic Garden has been conducted through compiling data records from PBGs Registration section, field inspection and observation to living collections in the garden, herbarium specimens and literature studies. The results show that total 17 wild Musa accessions has been recorded planted in Purwodadi Botanic Garden since 1990 until 2012; comprises of 8 Musa acuminata sub species, 2 Musa balbisiana forms, 1 Musa ornata, 1 Musa troglodytarum, 1 Musa borneensis and 4 unidentified species Musa spp.; but only 8 living accessions remained in 2012. Morpho-taxonomic review of those 8 wild Musa accessions remained will be discussed in this paper including their geographical distributions. According to its differentiated morphological characteristics observations, it is known that there are three accessions were resembled cultivars and one unidentified species have been determined its species level, so that their registration identity needs to be revised. It is important next to prioritize ex-situ conservation of wild Musa species not yet collected in Purwodadi Botanic Garden especially from Eastern Indonesia.